The Logic of Imagination: Classical Examples from Chinese Philosophy. Issue 2 (3rd April 2017) - Shaoming, Chen
EDITOR'S ABSTRACT: This article analyzes three well-known stories—the child about to fall in a well from Mencius, the butterfly dream in Zhuangzi, and the spear–shield contradiction in Han Feizi —to illustrate a type of philosophical argumentation that the author finds particularly inspiring but little explored in the reading of early Chinese texts. As opposed to the more speculative and abstract mode of philosophizing that has been largely imported from (or stimulated by) the West and that dominates at philosophy departments, a careful reflection on allegories, based on concrete experience and a lively imagination, leads to insights that are also universal and endlessly inspiring. Their interpretation can be very different from Western philosophical insights that seem similar at first sight.